The United Kingdom Infrared Telescope Infrared Deep Sky Survey first data release - Warren,SJ; Hambly,NC; Dye,S; Almaini,O; Cross,NJG; Edge,AC; Foucaud,S; Hewett,PC; Hodgkin,ST; Irwin,MJ; Jameson,RF; Lawrence,A; et al. (Monthly Notices of the Royal Astronomical Society, 2007)
The First Data Release (DR1) of the United Kingdom Infrared Telescope Infrared Deep Sky Survey (UKIDSS) took place on 2006 July 21. The UKIDSS is a set of five large near-infrared surveys, covering a complementary range of areas, depths and Galactic latitudes. The DR1 is the first large release of survey-quality data from the UKIDSS and includes 320 deg2 of multicolour data to (Vega) K= 18, complete (depending on the survey) in three to five bands from the set ZYJHK, together with 4 deg2 of deep JK data to an average depth K= 21. In addition, the release includes a similar quantity of data with incomplete filter coverage. In JHK, in regions of low extinction, the photometric uniformity of the calibration is better than 0.02 mag in each band. The accuracy of the calibration in ZY remains to be quantified, and the same is true of JHK in regions of high extinction. The median image full width at half-maximum across the data set is 0.82 arcsec. We describe changes since the Early Data Release in the implementation, pipeline and calibration, quality control, and archive procedures. We provide maps of the areas surveyed, and summarize the contents of each of the five surveys in terms of filters, areas and depths. The DR1 marks completion of 7 per cent of the UKIDSS seven-year goals.